KEEFEKTIFAN MEDIA ECENG GONDOK Eichornia crassipes DAN Eichornia azurea SEBAGAI FITOREMEDIATOR DALAM MENGABSORBSI Cr6+ DI LIMBAH CAIR PERTAMBANGAN NIKEL - Baharuddin; Dewi Safitri; Syahrul M (Universitas Hasanuddin, 2021)
Nickel is part of mining products. Nickel can be used for various human needs, but extracting nickel ore uses an open-pit method that produces liquid waste. CV. Unaha Bakti Persada uses sediment pond method and has 1.02 ppm of Cr6+, which is still above the standard quality standard of 0.1 ppm. This phenomenon is the basis for the need for Cr6+ liquid waste treatment through the phytoremediation method. The objectives of this study were to determine (1) the toxicity of Cr6+, (2) the reproduction of water hyacinths, (3) the absorption of Cr6+, and (4) the effectiveness of the phytoremediation method. The research used phytoremediation media of water hyacinth E. crassipes and E. azurea for 12 days and the experimental design was RAL with 2 factorials, 3 treatments and 2 repetitions. The results showed signs of toxicity in water hyacinth E. crassipes from Cr6 +, such as the faster the leaves dry out, the plants rot. The propagation of the vegetative phase only occurs in water hyacinth E. azurea, which is indicated by the presence of new stems and leaves. The absorption of water hyacinth E. crassipes 0.49 ppm, E. azurea 0.92 ppm and a combination of E. crassipes and E. azurea -0.47 ppm. The effectiveness of water hyacinth E. crassipes 48.04%, E. azurea 90.02% and the combination of E. crassipes and E. azurea -8.82%